2021
DOI: 10.4097/kja.20089
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between lactacidemia and postoperative complications after surgery for peritoneal carcinomatosis

Abstract: Background. Cytoreduction surgery has been developed as a treatment of peritoneal carcinomatosis. However, this surgery is associated with important complications. The present study attempts to assess the relationship between lactacidemia levels and the rate of associated complications in patients undergoing cytoreduction surgery during the immediate postoperative period in a critical unit. Methods. Retrospective observational study. 57 patients underwent cytoreduction surgery during the years 2014 and 2015 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The number (percentage) of the articles that received a score of 3 for the two items (parameters derived from statistical analysis methods and rationale for and details of statistical analysis methods) was 24 (77.4%) and 23 (74.2%), respectively. The studies by Lee et al [ 3 ] and Hervás et al [ 4 ] received scores of 2 for the “rationale for and details of the statistical analysis methods used” item because, although they stated that they used propensity score matching, no descriptions of the adjustment method, caliper value, or the ratio of pair-matching were found, which would significantly affect the results of the subsequent statistical analysis. Likewise, the papers by Lim et al [ 5 ] and Tamboli et al [ 6 ] reported performing statistical analyses without describing the rationale for and details of the statistical analysis methods used.…”
Section: Resultsmentioning
confidence: 99%
“…The number (percentage) of the articles that received a score of 3 for the two items (parameters derived from statistical analysis methods and rationale for and details of statistical analysis methods) was 24 (77.4%) and 23 (74.2%), respectively. The studies by Lee et al [ 3 ] and Hervás et al [ 4 ] received scores of 2 for the “rationale for and details of the statistical analysis methods used” item because, although they stated that they used propensity score matching, no descriptions of the adjustment method, caliper value, or the ratio of pair-matching were found, which would significantly affect the results of the subsequent statistical analysis. Likewise, the papers by Lim et al [ 5 ] and Tamboli et al [ 6 ] reported performing statistical analyses without describing the rationale for and details of the statistical analysis methods used.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Gruttadauria et al discovered a significant association between hyperlactatemia observed during the perioperative period of pancreatic cancer resection and a longer ICU stay [ 24 ]. Similarly, Hervás et al reported that a high LA level was a risk factor for postoperative complications in patients undergoing peritoneal cytoreductive surgery, resulting in an extended ICU length of stay [ 25 ]. LDH, which is the final enzyme in the lactate pathway and the end product of anaerobic glucose glycolysis, has also been identified as an independent risk factor in various types of cancer [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactate is one of the metabolites from glucose metabolism that has been identified as an oncometabolite in many cancers. Elevated lactate levels in the serum have been associated with poor prognosis and postoperative complications in patients with peritoneal cancers [ 48 ]. Lactate not only provides energy for the cancer cells but also regulates the TME by promoting angiogenesis, immunosuppression, and ECM remodeling [ 38 ].…”
Section: Dysregulated Metabolism Oncometabolites and Peritoneal Cance...mentioning
confidence: 99%